Establishing regulatory sandboxes for FinTech companies in the European Union to foster the development of the FinTech Sector – an analysis - Engelhardt, Linus (2021)
This paper aims to find an answer to the question whether and to what extent the concept of a Regulatory Sandbox for FinTech companies should be applied at the supranational level of the European Union. In several steps the term "FinTech" will be narrowed down and its effects on the global financial sector analyzed. Afterwards, the three most common regulatory approaches are presented, whereby the Regulatory Sandbox is described in more detail using the sandbox of the Financial Conduct Authority from the United Kingdom as an example. Finally, the relevant regulatory authorities in the EU are discussed. The results make clear that the economic importance of FinTechs is increasing significantly. Considering the fact that FinTechs from Great Britain account for almost three quarters of the total market volume, it is still clear that the EU must become much more attractive in the face of the coming Brexit in order not to lose ground globally. One way to do so is to provide regulatory certainty. A regulatory sandbox is suitable for this purpose, as it reduces uncertainty for companies and makes them more attractive for investors. Regulators also benefit from receiving direct feedback on their regulatory framework and being able to adapt and develop it accordingly. It is proposed that in the run-up to a joint European sandbox, interested National States establish their own national sandboxes, whereby all of them should decide slightly differently on both the structure and the objectives. Based on the experiences of the National States, it is up to the competent authorities in the EU to prepare a supranational sandbox. When implementing the establishment of such sandbox, clear coordination and responsibility of the actors as well as the assumed demand and potential problems have to be considered carefully.